Pelaksanaan dan pencapaian program kepolisan komuniti di Malaysia - Ismail, Nur Qurratul`Aini; Ngah, Kamarudin; Mustaffa, Jamaludin (Sekolah Pembangunan Sosial, 2018)

(untitled)
The effectiveness of Community Policing has been enhanced when PDRM has introduced two strategies namely ‘Ops Payung’ and sector cards that bring closer police personnel to the community or in other words ‘public engagement’. In Malaysia, based on the community’s policing, the community needs the presence of policemen. Unlike the outside world, their community members do not need the presence of police personnel everywhere. The crime prevention concept of Community Policing has long been established. The implementation of the current schemes, the Residents and Rukun Tetangga Association has helped a lot in preventing criminal activity in the surrounding communities. Among the current schemes currently and in Malaysia are the Salleh System, Partner Cop, Voluntary Patrolling Scheme, People’s Volunteer Corps, Police Volunteers, Department of Public Defense Malaysia, Amanita, Motorcycle Patrol Unit and National Blue Ocean Strategy. The implementation and achievement of community policing programs in Malaysia based on eleven organizations under the community policing demonstrate strongly in assisting PDRM especially in combating crime today. Therefore, with these organizations, it will also alleviate the task of members of the PDRM where the community has joined the members in full control of public safety. Now the community together with PDRM is in touch with each other in ensuring that the safety of the locals is always safe from the threat of crime.